2019
DOI: 10.1289/ehp4648
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Temperature and Markers of Fetal Growth: A Retrospective Observational Study of 29 Million U.S. Singleton Births

Abstract: Background:Emerging studies suggest that ambient temperature during pregnancy may be associated with fetal growth, but the existing evidence is limited and inconsistent.Objectives:We aimed to evaluate the association of trimester-specific temperature with risk of being born small for gestational age (SGA) and birth weight—markers of fetal growth—among term births in the contiguous United States.Methods:We included data on 29,597,735 live singleton births between 1989 and 2002 across 403 U.S. counties. We estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 61 publications
1
68
0
Order By: Relevance
“…In a second study using this data set, the researchers looked at the relationship between average ambient temperatures across the entire pregnancy and markers of fetal growth 9. They concluded that among full-term babies, those whose mothers were exposed to outdoor temperatures above the 90th percentile, averaged across the pregnancy, tended to have a slightly lower birth weight—equivalent to a mean 15g (about 0.5 oz) 17. Similar associations were reported for the second and third trimesters.…”
Section: Preterm Birth and Lbwmentioning
confidence: 82%
See 1 more Smart Citation
“…In a second study using this data set, the researchers looked at the relationship between average ambient temperatures across the entire pregnancy and markers of fetal growth 9. They concluded that among full-term babies, those whose mothers were exposed to outdoor temperatures above the 90th percentile, averaged across the pregnancy, tended to have a slightly lower birth weight—equivalent to a mean 15g (about 0.5 oz) 17. Similar associations were reported for the second and third trimesters.…”
Section: Preterm Birth and Lbwmentioning
confidence: 82%
“…However, the work continues. Most recently, in 2019, researchers at the Brown University School of Public Health published two reports based on data from the National Center for Health Statistics on approximately 30 million singleton births across 403 U.S. counties 9 , 17. In their study of preterm birth,9 the researchers defined “extreme heat” as temperatures above the 95th percentile of each county-specific temperature distribution.…”
Section: Preterm Birth and Lbwmentioning
confidence: 99%
“…The review was not designed to assess associations between low temperature and birth outcomes, though these were documented in several studies, most of which reported U shaped associations between temperature and outcomes. 46 51 61 62 64 79 86 87 Links between exposures to cold and other outcomes, such as mortality, are well documented. Little attention is paid to these links when climate change is discussed, even though the changes in climate which are occurring encompass both increases in temperatures and periods of low temperature extremes.…”
Section: Discussionmentioning
confidence: 99%
“…Estimations of the impacts of temperature exposure during early pregnancy should be especially affected. Indeed, the most reliable estimates show that the effect of first trimester exposure to a hot temperature on birth weight is much weaker than the effect of exposure to a hot temperature during the second and third trimesters 45 47 , which is consistent with a selection-induced upward bias, although other factors may also play a role. More importantly, our empirical approach offers a tool that can be used for the estimation of a corrected scarring effect.…”
Section: Discussionmentioning
confidence: 96%